The New Environmental Security: Linking Food, Water, and Energy for Integrative and Diagnostic Social-ecological Research - Philip A. Loring; S. Craig Gerlach; Henry P. Huntington (Journal of Agriculture, Food Systems, and Community Development, 2016)
In this commentary we describe a new framework for environmental security, one that draws food, water, and energy security into a unified socio-ecological research program. While traditional uses of environmental security carry statist and militaristic undertones, we propose that this "new" environmental security provides a more comprehensive perspective for research and development. Individually, food, water, and energy security research have made great progress, and as we describe here, the three have converged upon a core set of constituent properties: availability, access, utility, and stability. Yet, tradeoffs and interactions between food, water, and energy systems, which we argue tend to be place-based and which we illustrate using some examples from Alaska, are infrequently researched and not well captured in most global frameworks for integrated assessment. We present this integrative framework for environmental security, and conclude with suggestions regarding broad research themes and priorities.